2017
DOI: 10.1113/jp274111
|View full text |Cite
|
Sign up to set email alerts
|

The highs and lows of programmed cardiovascular disease by developmental hypoxia: studies in the chicken embryo

Abstract: It is now established that adverse conditions during pregnancy can trigger a fetal origin of cardiovascular dysfunction and/or increase the risk of heart disease in later life. Suboptimal environmental conditions during early life that may promote the development of cardiovascular dysfunction in the offspring include alterations in fetal oxygenation and nutrition as well as fetal exposure to stress hormones, such as glucocorticoids. There has been growing interest in identifying the partial contributions of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 115 publications
(296 reference statements)
1
33
0
Order By: Relevance
“…[7][8][9][10] In 2017, Li et al 11 demonstrated that CoCl 2 -induced hypoxia promoted cell migration and proliferation in placenta-derived mesenchymal stem cells. [7][8][9][10] In 2017, Li et al 11 demonstrated that CoCl 2 -induced hypoxia promoted cell migration and proliferation in placenta-derived mesenchymal stem cells.…”
mentioning
confidence: 99%
“…[7][8][9][10] In 2017, Li et al 11 demonstrated that CoCl 2 -induced hypoxia promoted cell migration and proliferation in placenta-derived mesenchymal stem cells. [7][8][9][10] In 2017, Li et al 11 demonstrated that CoCl 2 -induced hypoxia promoted cell migration and proliferation in placenta-derived mesenchymal stem cells.…”
mentioning
confidence: 99%
“…Several mammalian models have helped to unravel the biology and pathobiology of the ductus arteriosus (DA) and to understand the factors responsible for its closure or patency after birth. However, these models are technically complex and experimental manipulations affect both the mother and the fetus [1,2]. Therefore, there is a need for additional models, addressing these limitations.…”
Section: The Chicken Embryo As a Model For Ductus Arteriosus' Developmentioning
confidence: 99%
“…Correctly diagnosing arrhythmia and recognising complex arrhythmia have been signi cant goals in the history of modern electrocardiology [1]. Arrhythmia monitoring is an important type of long-term electrocardiogram (ECG) monitoring that is mainly used to detect arrhythmias, diagnose CVD in the early stages, evaluate anti-arrhythmic treatment, understand the relationship between premature ventricular contraction (PVC) and sudden death, perform electrophysiological studies of arrhythmia, and evaluate drug treatment effects [2][3]. Therefore, arrhythmia monitoring is critical for clinical analysis.…”
Section: Introductionmentioning
confidence: 99%